A new species of the genus Phytocoris (Hemiptera: Miridae), with an identification key to amygdali-group species of the subgenus Compsocerocoris found in Iran - Hosseini, Reza; Mohammadi, Saadi (Zootaxa, 2019)
A new species, Phytocoris (Compsocerocoris) darakiensis sp. nov. is described from Kurdistan province, Iran. A taxonomic key to the species of amygdali-group of the subgenus Compsocerocoris Reuter known in Iran, male and female habitus photographs and illustrations of male genitalia of the new taxon are provided. Diagnosis of the new species is based on a comparison with other congeneric found from Iran. The type specimens were deposited in the insect collection of the University of Guilan, Rasht, Iran.